Consumers Attitude Towards Skippable ADS on Youtube Trueview In-Stream - an Empirical Study Among College Students in Bandung - Saputra, Tejo Sandi; Fachira, Ira (Journal of Business and Management, 2014)
This study focuses on how young people respond to the YouTube TrueView in-stream as well as the factors that influence. Here, the ad will appear before the original video is playing and has an option